Pengaruh Pembangunan Manusia dan Pertumbuhan Ekonomi terhadap Kemiskinan di Indonesia Periode 2010 - 2018 - Anugerah Mardiansyah; Mohammad Saleh; Siswoyo Hari Sentosa (Jurnal Ekuilibrium, 2021)
One of the national development goals is to reduce the poverty level. Poverty is one of the diseases in the economy, so it must be cured or at least reduced. One indicator of the level of welfare of the population of a region is the human development index and economic growth proxied through GRDP. In this study, it will be seen how the influence of the human development index and Gross Reginal Domestic Product (GRDP) variables on poverty in Indonesia. The method used is Ordinary Least Square with quarterly data from 2010 - 2018 in Indonesia. The results of this study are that there is a negative and significant influence between the human development index and economic growth on poverty in Indonesia.